A statistical analysis of the influence of the journal of contract law in commonwealth court decisions - GOH, Yihan (Institutional Knowledge at Singapore Management University, 2018)
It is often said that 'A picture paints a thousand words'. In this instance, we would say that 'Tables and Graphs paint a vivid picture' instead. Indeed, apart from this very short introduction of sorts, we will mainly let the relevant tables and graphs speak for themselves - and more eloquently at that. The data which these tables and graphs present is, admittedly, more quantitative in nature; after all that is the quintessential quality of statistical analysis in general.A Statistical Analysis of the Influence of the Journal of Contract Law in Commonwealth Court Decisions (2018) 35 JCL 14